Intensive care following in-hospital cardiac arrest / periarrest calls—experience from one Scottish hospital - Andrew R. McCallum; Richard Cowan; Kevin D. Rooney; Paul C. McConnell (Journal of Anesthesia, Analgesia and Critical Care, 2024)
Abstract Background In-hospital cardiac arrest/periarrest is a recognised trigger for consideration of admission to the intensive care unit (ICU). We aimed to investigate the rates of ICU admission following in-hospital cardiac arrest/periarrest, evaluate the outcomes of such patients and assess whether anticipatory care planning had taken place prior to the adult resuscitation team being called. Methods Analysis of all referrals to the ICU page-holder within our district general hospital is between 1st November 2018 and 31st May 2019. From this, the frequency of adult resuscitation team calls was determined. Case notes were then reviewed to determine details of the events, patient outcomes and the use of anticipatory care planning tools on wards. Results Of the 506 referrals to the ICU page-holder, 141 (27.9%) were adult resuscitation team calls (114 periarrests and 27 cardiac arrests). Twelve patients were excluded due to health records being unavailable. Admission rates to ICU were low — 17.4% for cardiac arrests (4/23 patients), 5.7% (6/106) following periarrest. The primary reason for not admitting to ICU was patients being “too well” at the time of review (78/129 — 60.5%). Prior to adult resuscitation team call, treatment escalation plans had been completed in 27.9% (36/129) with Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) forms present in 15.5% of cases (20/129). Four cardiac arrest calls were made in the presence of a valid DNACPR form, frequently due to a lack of awareness of the patient’s resuscitation status. Conclusions This study highlights the significant workload for the ICU page-holder brought about by adult resuscitation team calls. There is a low admission rate from these calls, and, at the time of resuscitation team call, anticipatory planning is frequently either incomplete or poorly communicated. Addressing these issues requires a collaborative approach between ICU and non-ICU physicians and highlights the need for larger studies to develop scoring systems to aid objective admission decision-making.